2013
DOI: 10.1021/jo400616r
|View full text |Cite
|
Sign up to set email alerts
|

Copper-Catalyzed Decarboxylative Coupling of Alkynyl Carboxylates with 1,1-Dibromo-1-alkenes

Abstract: A copper-catalyzed decarboxylative coupling reaction of potassium alkynyl carboxylates with 1,1-dibromo-1-alkenes was developed for the synthesis of unsymmetrical 1,3-diyne and 1,3,5-triyne derivatives. Diverse aryl, alkenyl, alkynyl, and alkyl substituted 1,1-dibromo-1-alkenes can react smoothly with aryl and alkyl substituted propiolates to produce unsymmetrical 1,3-diynes and 1,3,5-triynes with high selectivity and good functional group compatibility.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

0
16
0

Year Published

2013
2013
2020
2020

Publication Types

Select...
6
4

Relationship

0
10

Authors

Journals

citations
Cited by 47 publications
(16 citation statements)
references
References 78 publications
0
16
0
Order By: Relevance
“…Fu et al reported that copper‐catalyzed decarboxylative coupling of potassium alkynyl carboxylates with 1,1‐dibromo‐1‐alkenes could produce 1,3‐diynes (Scheme , Eq. D) 17. However, the coupling reactions mentioned above were all carried out in organic solvents, and/or required the addition of the oxidant (e.g.…”
Section: Introductionmentioning
confidence: 99%
“…Fu et al reported that copper‐catalyzed decarboxylative coupling of potassium alkynyl carboxylates with 1,1‐dibromo‐1‐alkenes could produce 1,3‐diynes (Scheme , Eq. D) 17. However, the coupling reactions mentioned above were all carried out in organic solvents, and/or required the addition of the oxidant (e.g.…”
Section: Introductionmentioning
confidence: 99%
“…1‐(Phenylbuta‐1,3‐diynyl)‐3‐(trifluoromethyl)benzene (3c): The product was obtained as white solid in 73 % yield. 1 H NMR (300 MHz, CDCl 3 ): δ = 7.33–7.38 (m, 3 H), 7.45 (t, J = 7.8 Hz, 1 H), 7.51–7.54 (m, 2 H), 7.59 (d, J = 7.8 Hz, 1 H), 7.67 (d, J = 7.8 Hz, 1 H), 7.76 (s, 1 H) ppm.…”
Section: Methodsmentioning
confidence: 99%
“…1,4‐Bis(4‐methoxyphenyl)buta‐1,3‐diyne (m‐3): 33,34 Yield 60 %. 1 H NMR (400 MHz, CDCl 3 ): δ = 7.45–7.43 (d, 4 H), 6.84–6.82 (d, 4 H), 3.79 (s, 6 H) ppm.…”
Section: Methodsmentioning
confidence: 99%